E-Government interoperability frameworks: a worldwide inventory - Lisboa, Ana Isabel Oliveira (2014)
An e-government Interoperability Framework (IF) is a document or group of documents that specify a set of common elements such as vocabularies, concepts, principles, policies, guidelines, recommendations, standards, and practices for agencies that wish to work together, towards the joint delivery of public services. IFs are seen by governments as promising instruments to boost the interoperability of their services and systems. Henceforth, many countries have created and published their IFs along the last years. To the best of our knowledge no study has been carried out so far in order to identify the comprehensive list of countries that already have an IF. We argue that the existence of such a list would be very useful and valuable for both practitioners and researchers communities. Hence, this study addresses the question which is the worldwide comprehensive list of countries that currently have an e-government Interoperability Framework? To answer this question a worldwide survey that combined a web survey and a web questionnaire was conducted. The aim of this paper is to describe the effort and procedure done in order to conduct the worldwide survey and to present the results achieved with it.